Anaerobic digestion of enzymatically treated dairy cow effluent [Resumo] - Eusebio, Ana (2020)
ABSTRACT: In Portugal, cattle production increased up to 91,000 t in 2016 (EUROSTAT, 2016) and has been contributing to the increase of methane emissions into the atmosphere. As an appropriate process for the treatment of organic effluents, anaerobic digestion is ideal to minimize this negative impact since it provides the agricultural and energetic valorisation of the substrate through the production of digestate and biogas. Heating, cooling and electricity supply constitute different applications for this energy carrier gas with a relevant social, environmental and economic importance, mainly for the region and neighbouring areas where it is produced. Dairy cow effluent is an example of lignocellulosic biomass, whose recalcitrant compounds, such as lignin and phenols, must be previously hydrolysed and made available for subsequent anaerobic digestion. The use of laccase and hemicellulase may be of great interest as pre-treatment for a wide range of pollutant compounds of effluents.